STUDI INTEGRASI SERTA KETERSEDIAAN SARANA DAN PRASARANA TRANSPORTASI UMUM DI KAWASAN STASIUN TENJO, KABUPATEN BOGOR - Alivia Putri Winata; Regina Suryadjaja; Suryadi Santoso; B. Irwan Wipranata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Tenjo Station is the main public transportation mode in Tenjo District which is one of the mobillity centers in the area. Tenjo Station is a stopping place for the Commuter Line which requires support from other modes of transportation to reach it hence a high quality transportation infrastructure is needed to be able to create interdependent integration. In addition, regional development can be a benchmark that requires integration between modes in forming an area. Therefore, to find out the conditions of integration and the availability of transportation facilities and infrastructure, it is carried out through network and movement analysis and analysis of transportation facilities and infrastructure using a descriptive-qualitative methods such as observational data, interviews and secondary data obtained from Google Maps and the Moovit application. Network and movement analysis is carried out by processing road network data that can be accessed to reach Tenjo Station. While the analysis of transportation facilities and infrastructure is carried out by processing data on stop points and routes from transportation modes with assessment tools standardization of bus stop making. In order to find out these conditions that are supported by the results of the two analyzes, development recommendations can be carried out by adding transportation infrastructure in the form of bus stop as a place to switch modes in order to create integration. As well as recommendations for the improvement of Tenjo Station as the main station so that it is more adequate in its use. Keywords:  Tenjo Station; Integration of Transportation Mode; Availability of Transportation Facilities and Infrastructure Abstrak Stasiun Tenjo merupakan moda transportasi umum utama di Kecamatan Tenjo yang merupakan salah satu pusat mobilitas pada kawasan tersebut. Stasiun Tenjo adalah tempat pemberhentian Kereta Rel Listrik (KRL) yang memerlukan dukungan dari moda tranportasi lain untuk dapat mencapai Stasiun Tenjo sehingga dibutuhkan prasarana transportasi yang baik untuk dapat menciptakan integrasi yang saling bergantung. Selain itu, pengembangan kawasan dapat menjadi tolak ukur bahwa diperlukan integrasi antar moda dalam membentuk suatu kawasan. Dengan demikian, untuk mengetahui kondisi integrasi dan ketersediaan sarana dan prasarana transportasi dilakukan melalui analisis jaringan dan pergerakan dan analisis sarana dan prasarana transportasi dengan metode deskriptif - kualitatif seperti data hasil observasi, wawancara serta data sekunder yang diperoleh dari Google Maps dan Aplikasi Moovit. Analisis jaringan dan pergerakan dilakukan dengan mengolah data jaringan jalan yang dapat diakses untuk mencapai             Stasiun Tenjo. Sedangkan analisis sarana dan prasarana transportasi dilakukan dengan mengolah data titik pemberhentian dan rute dari moda transportasi dengan alat penilaian standarisasi pembuatan bus stop. Dalam rangka mengetahui kondisi tersebut yang didukung dari hasil kedua analisis, rekomendasi pengembangan dapat dilakukan dengan penambahan prasarana transportasi berupa bus stop sebagai tempat peralihan moda agar terciptanya integrasi. Serta rekomendasi untuk dilakukan peningkatan Stasiun Tenjo sebagai stasiun utama agar semakin memadai dalam penggunaannya.